1994
DOI: 10.1139/l94-067
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of repeated loads and low temperatures on asphalt pavements

Abstract: This research was undertaken to study the combined effect of repeated vehicle loads and low temperatures on the design thickness for both recycled and virgin asphalt pavements. It included three parts of work: theoretical analysis, laboratory tests, and computation. In the theoretical analysis, the finite layer method was used instead of the conventional layered theory to obtain the relationship between vehicle loads and the mechanical parameters in the pavement layers. In the laboratory tests, the behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Fang and Sargious [13] evaluated the combined effect of repeated loads and low temperature on asphalt pavement's performance using laboratory indirect tensile strength test. The researchers conducted cyclic tests on an asphalt sample at various temperatures (−10 to 22°C) and concluded that fatigue damage is critical for greater temperature, i.e., 22°C.…”
Section: Introductionmentioning
confidence: 99%
“…Fang and Sargious [13] evaluated the combined effect of repeated loads and low temperature on asphalt pavement's performance using laboratory indirect tensile strength test. The researchers conducted cyclic tests on an asphalt sample at various temperatures (−10 to 22°C) and concluded that fatigue damage is critical for greater temperature, i.e., 22°C.…”
Section: Introductionmentioning
confidence: 99%